Extracellular vesicles and oncogenic signaling - Schubert, Antonia; Boutros, Michael (Molecular oncology, 2021)
Extracellular vesicles (EVs) emerged as potential diagnostic and prognostic markers for cancer therapy. This review summarizes mechanisms of signaling specificity and cargo transfer by EVs in the oncogenic and cancer-associated signaling cascades Wnt, TGF-β, ErbB, VEGF, and PD1-PD-L1. Translatable EV functions and existing knowledge gaps are discussed to possibly further exploit EVs for diagnostics and therapeutic approaches in the future.
Gesehen am 12.02.2024